Creatividad en los estudiantes de primer año de Bachillerato común paralelos A,B,C sección matutina del Colegio Nacional Mixto Simón Bolívar de la parroquia Puerto Bolívar cantón Machala provincia de El Oro 2012. - Orellana Aguilar, Lilia Alexandra (2012)
The purpose of this research is to promote the development of creativity in the students of the Simón Bolívar College of the First Year of High School Common parallels A, B, C morning section. The present study is inductive-deductive and observational-psychological in what has been taken a sample of the student population, teacher and parents.